ARTIFICIAL INTELLIGENCE AND BIG DATA AS DRIVERS OF SUSTAINABLE ECONOMIC GROWTH IN THE ERA OF DIGITALIZATION (INTERNATIONAL SCIENTIFIC-ELECTRONIC JOURNAL “PIONEERING STUDIES AND THEORIES”, 2025)
The integration of artificial intelligence (AI) and big data technologies has become a transformative force shaping the new architecture of global economic systems in the digital era. Their strategic application redefines mechanisms of production, distribution, and governance, enabling economies to achieve sustainable growth through efficiency, adaptability, and innovation. In developing countries such as Uzbekistan, the implementation of AI-driven analytics and dataintensive decision models serves as a foundation for improving productivity, optimizing resource allocation, and stimulating the digital competitiveness of enterprises. The study explores how intelligent data processing, machine learning algorithms, and predictive analytics collectively enhance economic sustainability by linking technological advancement with social inclusiveness and environmental responsibility. It also examines the institutional and policy dimensions necessary for integrating AI and big data into national digital strategies, emphasizing the importance of data ethics, regulatory adaptability, and human-capital readiness. The findings underline that the sustainable expansion of digital economies depends not only on technological investment but also on the synergy between governance, innovation ecosystems, and education systems capable of fostering advanced analytical competencies.